Stereotactic Body Radiation Therapy (SBRT) as Salvage Therapy for Oligorecurrent Pleural Mesothelioma After Multi-Modality Therapy - Schröder, Christina; Opitz, Isabelle; Guckenberger, Matthias; Stahel, Rolf; Weder, Walter; Förster, Robert; Andratschke, Nicolaus; Lauk, Olivia (Frontiers in Oncology, 2019)
Introduction: Therapy options for patients with oligoprogressive malignant pleural mesothelioma (MPM) are limited. Stereotactic Body Radiotherapy (SBRT) may be a promising therapeutic option, as it delivers a localized ablative dose of radiation and therefore balances efficacy and treatment related toxicities. The intent of this retrospective analysis was to evaluate the feasibility of SBRT for limited pleural recurrences. Methods and Material: This retrospective single-institution study is based on the 21 consecutive patients treated with hypofractionated radiotherapy for oligoprogressive MPM. Clinical and radiological data was collected at regular follow-up visits including toxicity, local control and survival. Results: At primary diagnosis, 57% of the patients presented with stage III disease. Initial treatment of MPM consisted of induction chemotherapy (n=12) prior to a macroscopic complete resection (n=18). 3 patients received additional intracavitary chemotherapy and another 3 patients were treated with chemotherapy alone without another treatment at the time of first diagnosis. A total of 50 lesions in recurrent MPM were treated with SBRT. The median number of radiotherapy fractions was 5 (range 3–20) with a median dose per fraction of 5 Gy (range 2.5–12.5 Gy). The median total treatment dose was 30 Gy (20–50 Gy) with a median prescription isodose line (IDL) of 65 % (65–100 %). Median follow-up of all patients from diagnosis was 28 months (range 7 – 152 months). Analysing all lesions separately, the 12-months-local control from SBRT was 73.5 %. The median PFS after SBRT was 6 months (range 0 – 21 months) and the median OS from first first SBRT was 29 months (range 0 – 61 months). Only 1 patients experienced above Grade 3 toxicities. Conclusion: This analysis demonstrates the feasibility of a SBRT approach for oligorecurrent MPM. SBRT was well tolerated even after multiple repetitions and local control was high with a promising median OS.